Association study of interleukin-1 receptor associated kinase 1 rs3027898 A?C gene polymorphism and preeclampsia in Pakistani population - Amna Mahmood; Amena Rahim; Muhammad Afzal; Muhammad Imran Bajwa; Yawar Zaman; Hira Waqas Cheema (Journal of the Pakistan Medical Association, 2021)
Objective: To find the association between interleukin- 1 receptor associated kinase 1 rs 3027898 gene polymorphism and preeclampsia in Pakistani population. Preeclampsia (PE) is defined as hypertension with proteinuria, diagnosed after 20 week of gestation up till 2 week postpartum. . It affects 2-8% of all pregnancies and remains a leading cause of maternal and perinatal deaths worldwide with around 344,000 women dying from preeclampsia in the last ten years. Incidence of preeclampsia in pregnant women in Pakistan is 1.2%. The World Health Organization (WHO) estimates that preeclampsia is responsible for 12% of maternal mortality in Asia. Continuous...